THE ROLE OF PUBLIC-PRIVATE PARTNERSHIPS IN SUPPORTING THE DIGITALISATION OF EDUCATION IN DEVELOPING COUNTRIES - Gunawan Widjaja (Adisam Publisher, 2025)
Public-private partnerships (PPPs) play a crucial role in supporting education digitalisation initiatives in developing countries. By combining the private sector's financial and technical resources with government efforts, these partnerships help provide vital technological infrastructure to schools in less developed areas. In addition, PPP initiatives also focus on strengthening the transfer of knowledge and skills through training and curriculum development relevant to the needs of the job market. This collaboration also encourages innovation, which enables the development and implementation of sustainable digital solutions to improve access to and quality of education. Overall, public-private partnerships are key to creating an education system that is inclusive and responsive to global changes in developing countries.